Implementation of Musyarakah Financing Contract Implementation at PT. Bank Sumut Syariah Katamso Medan - Ulil Azmi A Parinduri; Ahmad Perdana Indra (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2023)
This research was conducted at PT. Bank Sumut Syariah Branch Office of Brigadier General Katamso Medan. This study aims to determine the implementation of Musyarakah financing at Bank Sumut Syariah Branch Office of Brigadier General Katamso Medan. The analysis of this research uses descriptive qualitative analysis, which describes in writing the data that has been collected both written and oral obtained from the subject under study. The type of data used in this study is secondary data based on data from customers who use musyarakah financing in 2020-2021. The results showed that in implementing the profit-sharing financing system at Bank Sumut Syariah using Musyarakah contracts, banks and customers would benefit from their business. There are 79 debtors in 2020 and 84 debtors in 2021.